Design of pop up book based on realistic mathematics education to improving spatial ability students of class VIII - Bustanika, Luthf H; Suparman (Jurnal Pendidikan Bitara UPSI, 2019)
Spatial ability is about mentally manipulating things and their components and is considered critical for different domains such as science, technology, engineering, and mathematics, it was also can understanding the relation and nature of geometry to solve mathematical problems in everyday life. This study aims to design teaching materials in the form of pop up books based on Realistic Mathematics Education (RME) to improve students’ spatial ability in three-dimensional material. This type of research is the development research RnD (Research and Development) with the ADDIE model. This study discusses the design stage. The subjects of this study were teachers and students of eight-grade of Muhammadiyah Boarding School (MBS) Pleret Yogyakarta. The research data was obtained by interviewing to describe students’ needs, and learning information used, as well as document analysis to analyze curriculum, learning materials, and teaching materials. Data analysis techniques use qualitative analysis. This study produced a pop up book design that was in accordance with the analysis of student needs, student characteristics, curriculum, materials, learning methods, and teaching materials. Pop up books are designed based on RME and are designed to improve students’ spatial abilities. This research can be developed at the development, implementation, and evaluation.